The problems of humanization of professional traning of future engineers - Кокарєва, А.М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2012)
The article is conseded the problems of humanization of professional traning of engineers in technical universetes, that intended for humanization of technical education and training.